Mengkaji Makna Ritual Weda Rewa Tuke Mbaru dalam Hubungannya dengan Sakramen Perkawinan di Stasi Santo Fransiskus Xaverius Maras - Dionisius Ombot; Gerardus B. Duka; Petrus Tamelab (Berkat : Jurnal Pendidikan Agama dan Katolik, 2026)
This study was motivated by a shift in public understanding of the *weda rewa tuke mbaru* ritual, which is often regarded as the complete validation of marriage, leading some couples to live together before receiving the Catholic Sacrament of Marriage. This study aims to examine the meaning of the *weda rewa tuke mbaru* ritual, identify the factors causing misconceptions about it, and analyze its relevance to Christian values and Catholic family life. A qualitative method with a descriptive approach was employed. Data were collected through structured interviews and documentation involving 11 informants, including a priest, traditional elders, the station leader, the Basic Ecclesial Community (KUB) leader, married couples, and a catechist at St. Francis Xavier Station, Maras. The findings indicate that the *weda rewa tuke mbaru* ritual symbolizes respect for women and their families, serves as formal recognition of the relationship between the bride and groom, and functions as a social and moral bond within the Manggarai customary marriage tradition. The ritual also reflects the values of fidelity, responsibility, and togetherness, which are consistent with the teachings of the Catholic Sacrament of Marriage. However, misconceptions remain, as some people consider the ritual sufficient justification for cohabitation without receiving the sacrament. These misconceptions are influenced by limited religious understanding, modernization, and inadequate pastoral guidance. The study concludes that the ritual remains relevant when understood as a customary tradition that supports, rather than replaces, the Catholic Sacrament of Marriage.